Experimental Investigation of the Closed Loop Oscillating Heat Pipe Condenser for Vapor Compression Refrigeration. - Yeunyongkul, P. (Journal of Applied Science and Engineering)
The aim of this paper is to experimentally investigates the applying of the closed loop oscillating heat pipe (CLOHP) condenser in vapor compression refrigeration. Split type air conditioner for residence was considered with two disadvantages. Firstly, the large pressure drop was occured in the condenser because refrigerant flows inside very small copper tube. This pressure drop causes higher compressor power, resulting in decreasing of the Coefficient of Performance (COP). Secondly, a lot of wasted heat losses to surrounding since the refrigerant has to condense after passing through condenser. To recover pressure drop and heat from the condensing process, this research is pursued to use the CLOHP instead of the conventional condenser in split type air conditioner. The refrigerating capacity, refrigerant and working fluid were 12,500 Btu/hr, R22 and R123, respectively. The experimental results were obtained then compared with the conventional one. It can be seen that COP of the conventional condenser was higher than the CLOHP condenser while energy efficiency rating (EER) of the conventional condenser was lower than the CLOHP condenser. In addition, the pressure drop in a refrigerant line of the CLOHP condenser was lower than that of the conventional condenser. Finally, 3 degree celcius increasing of water temperature, which recovers heat from condenser section of CLOHP, was obtained from utilization.